Protective effects of molsidomine against doxorubicin-induced renal damage in rats - Oguz, Fatih; Beytur, Ali; Sarihan, Ediz; Oguz, Hilal K.; Bentli, Recep; Samdanci, Emine; Ekinci, Nihat (Canadian Soc Clinical Investigation, 2016)
Purpose: The purpose of this study was to investigate the therapeutic and protective effects of molsidomine (MLS) against doxorubicin (DOX)-induced renal damage in rats. Methods: Forty rats were randomly divided into five groups (control, MLS, DOX, DOX+MLS and MLS+DOX groups). Thiobarbituric acid reactive substance (TBARS), reduced glutathione (GSH), superoxide dismutase (SOD), catalase (CAT), nitric oxide (NO) and glutathione peroxidase (GPx) levels were determined from kidney tissues and blood urea nitrogen (BUN), creatinine (Cr) and albumin (Alb) levels also determined. Results: DOX treatment caused a significant increase in TBARS levels and a significant decrease in the GSH and CAT levels compared with the control group. In comparison, MLS administration before DOX injection caused a significant decrease in TBARS levels and also increases in GSH and CAT levels, whereas treatment of MLS after DOX injection did not show any beneficial effect on these parameters. All groups showed a significant increase in NO levels compared to the control group. There were no significant differences among the all groups for BUN and Cr levels. Serum level of Alb decreased in the DOX-treated groups when compared with control and MLS groups. The histopathological findings were in accordance with the biochemical results. MLS treatment reversed the DOX-induced kidney damage in group 4. MLS treatment before DOX injection exerted a protective effect against DOX-induced kidney damage. Conclusions: MLS shows promise as a possible therapeutic intervention for the prevention of kidney injury associated with DOX treatment. Additional studies are warranted.
Keywords: Ischemia-Reperfusion Injury; Acid Phenethyl Ester; Nitric-Oxide; Induced Nephrotoxicity; Toxicity; Cardiomyopathy; Aminoguanidine; Glutathione; Inhibition; Apoptosis